The “keep in the ground future” of Arctic fossil fuel resources - LANSETTI, SANDI (Arctic and North, 2016)
It is extremely important to understand which role Arctic fossil fuel resources will play in the development and geopolitics of the Arctic region. The article analyses the recent trends in the world energy supply with speci al focus on renewable energy and future demand for fossil fuels. Focusing on the Arctic LNG projects it comes to the conclusion that there is a growing possibility that the majority of Arctic oil and natural gas will be kept in the ground. Such an outcome would strongly influence the sustainable development and geopolitics of the region.